Kemampuan dan Kesulitan Siswa Kelas X SMA Negeri 3 OKU dalam Menulis Teks Negosiasi - Dhania, Esta Rahma; Anam, Samsul; Awalludin, Awalludin (UNIB Press, 2019)
The purpose of this study was (1) to describe the ability of class X students of SMA Negeri 3 OKU in write negotiating text and (2) to describe the difficulties of class X students of SMA Negeri 3 OKU in write negotiating text. The method used in this research is quantitative descriptive. The data collection technique used in this study is performance test and questionnaires. The data analysis technique used is descriptive statistical analysis technique. The test results show that from 33 people, students who scored 80—100 with a very capable category numbered 12 people (36.36%), students who scored 66—79 with a capable category amounted to 12 people (36.36%), students those who get grades of 56—65 with a category of capable enough amount to 6 people (18.18%), students who score 46—55 with a category of underprivileged number of 3 people (9.09%), and there are no students who get a score categorized as a failure. The average value of students writing negotiating texts is 72.09. Thus, the ability of students to write negotiating texts is quite capable. Based on the results of questionnaire data analysis, it is known that the difficulties faced by students in writing negotiating text are that students often have difficulty determining the right choice of words because of their limited understanding of diction and students often have difficulty in determining the structure of negotiating text writing.